Preference for young workers in mid-career recruiting using online ads for sales jobs: Evidence from Japan - Mirka Zvedelikova (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This study uses an original dataset of online mid-career job ads for full-time sales jobs collected from July 2018 to December 2019 to examine the use of explicit and implied age limits on job applicants and characteristics of companies that set them. Although Japanese law prohibits age discrimination in employment, several exemptions are allowed, such as hiring young workers without prior work experience on regular contracts. Companies can set an age limit, require job-related experience, or search broadly; however, they can also express their age preference in other ways. In the sample, 24% of ads included explicit age limits generally capped at 35 years, 22% set experience requirements, and nearly all contained some form of implied age preference. Companies with higher capital, those with fewer employees, older companies and those located in urban centers tend to set requirements on applicants. Further, companies that are domestic, with fewer employees, in urban centers and companies using probation periods for new hires are more likely to set age limits. Furthermore, the role of company market power is considered a factor allowing companies to voluntarily limit the pool of applicants in a tight labor market. Companies that set age or experience requirements appear not to engage in wage competition related to labor market tightness. Companies that do not set either requirement partially respond to increased wage expectations related to population age while reducing labor costs by increasing working hours covered by the baseline salary.
Keywords: J42; J63; J71; 330; Mid-career recruiting; Age discrimination; Job ads; Monopsony; Japan